2021
DOI: 10.1371/journal.pone.0245875
|View full text |Cite
|
Sign up to set email alerts
|

Effects of circuit training or a nutritional intervention on body mass index and other cardiometabolic outcomes in children and adolescents with overweight or obesity

Abstract: Objective We aimed to assess the effectiveness of the first 6 months of a 24 month multidisciplinary intervention program including circuit training and a balanced diet in children and adolescents with obesity. Methods A quasi-experimental intervention trial included 242 participants (age [mean±standard deviation]: 11.3±2.06 years, 97 girls) of at least 85th percentile of age- and sex-specific body mass index (BMI). Participants were grouped into three to receive usual care (usual care group), exercise inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 49 publications
0
37
0
Order By: Relevance
“… 53 A recent trial published its results from the first 6 months of a 24-month multidisciplinary intervention approach that included a balanced diet and circuit training among 242 children and adolescents aged 6 to 17 years with obesity. 54 The preliminary data showed improvement in BMI z-score (−0.14) in the exercise group and reduction in adiponectin and waist circumference, however they could find a significant decrease in HOMA-IR. Interestingly they performed a sensitivity analysis based on puberty stage and found significant reduction in HOMA-IR when considering pubertal participants only.…”
Section: Managementmentioning
confidence: 88%
See 2 more Smart Citations
“… 53 A recent trial published its results from the first 6 months of a 24-month multidisciplinary intervention approach that included a balanced diet and circuit training among 242 children and adolescents aged 6 to 17 years with obesity. 54 The preliminary data showed improvement in BMI z-score (−0.14) in the exercise group and reduction in adiponectin and waist circumference, however they could find a significant decrease in HOMA-IR. Interestingly they performed a sensitivity analysis based on puberty stage and found significant reduction in HOMA-IR when considering pubertal participants only.…”
Section: Managementmentioning
confidence: 88%
“…Interestingly they performed a sensitivity analysis based on puberty stage and found significant reduction in HOMA-IR when considering pubertal participants only. 54 Also, a meta-analysis which included 24 studies that assessed the effects of physical activity on fasting insulin showed positive effects in improving fasting insulin as a marker of pediatric insulin resistance, with the greater effects seem among those with higher BMI z-scores. 55 Different training interventions such as resistance, aerobic and circuit training were used between studies, as well as non-traditional games to encourage an increase in levels of physical activity.…”
Section: Lifestyle Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous research, the effectiveness of adding an intensive exercise component to a lifestyle intervention for children and adolescents is high for reducing BMI in the short term [20,21]. The short-term effects of adding an exercise program were significant in the ICAAN study as well, as the exercise group was the most successful in decreasing zBMI after 6 months of intervention, according to a previous paper on the ICAAN study [22]. Contrary to our expectations, the long-term effects of adding an exercise component to a multidisciplinary lifestyle intervention were not significantly different from the other groups who experienced more gradual weight loss.…”
Section: Discussionmentioning
confidence: 84%
“…The longitudinal Intervention for Childhood and Adolescent Obesity via Activity and Nutrition (ICAAN) study is a 2-year quasi-experimental intervention trial (cris.nih.go.kr, KCT0002718) to test interventions that can prevent excessive weight gain and improve several health indices in obese children and adolescents, which was conducted from August 2016 to May 2019. The study design and the effectiveness of the first 6 months of this program have previously been described [13]. In brief, 242 overweight, obese, and severely obese individuals were recruited into the ICAAN study and then assigned to three treatment groups as follows: usual care for obesity, including counseling on diet, physical activity and behavioral modification (usual care group); exercise intervention (exercise group); intensive nutritional and feedback intervention (nutritional group) group.…”
Section: Study Participantsmentioning
confidence: 99%